2018
DOI: 10.3390/ijerph15071430
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor for Incident Functional Disability and the Effect of a Preventive Exercise Program: A 4-Year Prospective Cohort Study of Older Survivors from the Great East Japan Earthquake and Nuclear Disaster

Abstract: Objective: The aim of this study is to assess the risk factors for incident functional disability among long-term evacuees of Iitate village after Great East Japan Earthquake and nuclear disaster (GEJE). We also investigated the effectiveness of exercise classes as an intervention measure in this situation. Methods: 1159 subjects (75.2 ± 5.8 years, 57.5% female) were included at baseline, and followed-up for four years. Cox proportional hazard regression analysis was used to estimate the hazard ratio (HR) of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…They have been at the forefront of dialogues with the residents since the very early stage of the accident. Their role is to provide community members health-related advice, but it has become difficult in the nuclear accident aftermath (Kuroda et al, 2018a(Kuroda et al, , 2018b. Together with a psychologist from Fukushima Medical University, they initiated various actions, especially, round-table dialogues in all 'Kasetsu' (temporary houses) and a nursery for young children from Iitate.…”
Section: Box 1 a Summary Presentation Of The Co-expertise Initiativementioning
confidence: 99%
“…They have been at the forefront of dialogues with the residents since the very early stage of the accident. Their role is to provide community members health-related advice, but it has become difficult in the nuclear accident aftermath (Kuroda et al, 2018a(Kuroda et al, , 2018b. Together with a psychologist from Fukushima Medical University, they initiated various actions, especially, round-table dialogues in all 'Kasetsu' (temporary houses) and a nursery for young children from Iitate.…”
Section: Box 1 a Summary Presentation Of The Co-expertise Initiativementioning
confidence: 99%
“…Previous research has indicated that long-term evacuees experienced multiple stressors, including uncertainty about the future, lifestyle changes, and psychological stress, which have resulted in deterioration of both physical and mental health [ 11 , 12 , 13 , 14 ]. Analysis of the relationship between the evacuees’ living environment and their levels of mental health and social support indicated that those residing in rental apartments had poorer mental health and more difficulty getting social support than those residing in temporary housing [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional disability is a significant problem after natural disasters, especially among elderly survivors [1]. The Great East Japan Earthquake (GEJE) and tsunami destroyed the northeast coastal region of Japan in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing functional decline is an important issue after natural disasters and should be considered even during the disaster recovery period. The environmental habitat changed and many evacuees lost connections with their local communities after the GEJE [1, 5]. Because older survivors are more vulnerable to these changes, they have had fewer opportunities to go out into the community.…”
Section: Introductionmentioning
confidence: 99%